Pathways to incarceration: an examination of childhood maltreatment and personality psychopathology in incarcerated adults. Issue 3 (16th March 2021) - Boland, Jennifer; Rock, Rachel; Johnson, Alexandria K.; Jones, Michelle A.; Salekin, Randall T.; Anderson, Jaime L.
ABSTRACT: Early-life exposure to childhood maltreatment, whether physically-, emotionally-, and/or sexually-based has been linked consistently to psychological distress throughout the lifespan, including the development of personality disorders (PDs). Individuals with PD diagnoses are at an increased risk for criminal behavior, and borderline and antisocial PDs are particularly common in forensic settings. However, little research has assessed associations among all three variables: childhood maltreatment, personality psychopathology, and adult criminal behavior. The current study sought to address this gap in the literature by examining the associations among childhood maltreatment, maladaptive personality domains, and adult criminal behavior broadly, as well as examining the mediation pathway from childhood maltreatment to maladaptive personality to adult criminal behavior. Data collection for the current study occurred at a county jail in the Southern United States ( n = 180), where participants were administered self-report measures of demographics, adult arrest history, maladaptive personality, and childhood trauma. Pearson correlation and path analyses were used to examine the data, and support was found for both broad associations of childhood maltreatment with maladaptive personality domains and adult criminal behavior, and a relationship between childhood maltreatment and adult criminal behavior, which was mediated by maladaptive personality. Implications and directions for future research are discussed.